Genetic dissection of grain traits and their corresponding heterosis in an elite hybrid - Zafar, Sundus; You, Hui; Zhang, Fan; Zhu, Shuang Bin; Chen, Kai; Shen, Congcong; Wu, Hezhou; Zhu, Fangjin; Zhang, Conghe; Xu, Jianlong (Frontiers in Plant Science, 2022)
The successful implementation of heterosis in rice has significantly enhanced rice productivity, but the genetic basis of heterosis for grain type and grain weight remains unclear. To investigate the genetic dissection of heterosis for grain shape and grain weight and their relationship with grain yield in indica/xian rice, quantitative trait locus (QTL) mapping was conducted using 1,061 recombinant inbred lines (RILs) derived from a cross of the xian rice cultivars Quan9311B (Q9311B), and Wu-shan-si-miao (WSSM), and a backcross F1 (BC1F1) population developed by crossing the RILs with Quan9311A (Q9311A) combined with phenotyping in Hefei (HF) and Nanning (NN) environments. A total of 126 main-effect (M-QTL) and 370 epistatic QTL (E-QTL) were identified for 1000-grain weight (TGW), grain yield per plant (GYP) and grain shape including grain length (GL), grain width (GW), and grain length to width ratio (GLWR) in the RIL, BC1F1, and mid-parent heterosis (HMPs) populations. Differential detection of QTL in three populations revealed that most additive loci observed in the RILs did not have heterotic effects, but some did contribute to BC1F1’s performance. However, 26 M-QTL not only contributed to BC1F1’s performance but also contributed to heterosis. A total of seven QTL regions was identified, which simultaneously affected grain shape, weight, and grain yield traits in the same environment, including five regions with opposite directions and two regions with consistent directions of favorable allele effects for grain type, weight and grain yield traits, indicating the presence of partial genetic overlaps between grain shape or weight and grain yield, respectively. This study suggested different approaches for developing high yield and good grain quality by introgressing or pyramiding favorable alleles with the consistent direction of gene effect at the QTL regions affecting grain shape/weight and grain yield distributing on different chromosomes, or introgressing or pyramiding favorable alleles into the parents then fixing additive effects in hybrid as well as pyramiding the polymorphic overdominant/dominant loci between the parents and eliminating underdominant loci from the parents. These outcomes offer valuable information and strategy to develop hybrid with high yield and good grain quality with suitable grain type and weight.